Highly Structured Treatment Programs for Addicted Offenders: Comparing the Effects of the Reasoning & Rehabilitation Program and DBT-F - Wettermann, Anne; Völlm, Birgit; Schläfke, Detlef (Frontiers in Psychiatry, 2020)
Background: When treating addicted offenders in a forensic psychiatric setting, a primary concern is to decrease antisocial cognitions and behaviors. The cognitive style of offenders is often characterized by impulsiveness, egocentricity, irrational thinking and rigidity. We examined the relative efficacy of R&R and DBT-F on the domains of underlying psychological constructs (e.g., mental flexibility, planning and problem-solving). Materials and Methods: The Reasoning and Rehabilitation Program (R&R) and Dialectical Behavioral Therapy– Forensic (DBT-F) were introduced in a forensic-psychiatric hospital for offenders with substance addictions in Germany. We compared pre- and post-tests to measure the cognitive skills of addicted offenders having undergone R&R (N = 47), DBT-F (N = 34) or Treatment as Usual (TAU; N = 28). Participants’ skills (cognitive flexibility, ability to inhibit cognitive interference, cognitive performance/ mental speed, divergent and convergent reasoning/ problem solving) were assessed using neuropsychological instruments. Analyses of variance were conducted to investigate whether there were significant improvements within groups and whether these differences were significant between groups. To examine the predictive power of treatment -program on outcomes, and diagnosis of personality disorder, a hierarchical regression model was used. Results: Both programs were associated with improvements in nearly all of the measured constructs. The only construct on which the R&R and DBT-F groups differed significantly was word fluency, with those receiving R&R improving more than those receiving DBT-F. A regression model showed no predictive power for age, IQ or diagnosis of personality disorder. Treatment group explained 13.8% of variance in cognitive flexibility, but did not predict variance in other outcomes. Conclusion: Surprisingly, we did not find superiority for one intervention over TAU or differential effects between the two programs. Future research should use larger samples and additional outcomes, including recidivism, to identify possible effects of treatment programs. Additionally, qualitative methods might inform us about these programs are implemented as well as which outcomes may be relevant.